Dental esthetics and its effect on psychological well-being in a university hospital in Riyadh, KSA - Yasmine Tarek Ahmed; Abdulrahman Al Saffan; Atheer Saleh Al Malky; Haila Ahmed Al Nughaimshi; Reem Jasir Al Herbisch; Reema Ebrahim Al Yahya; Sultana Mohammed Al Zain (Wolters Kluwer Medknow Publications, 2020)
Background: The importance of dental esthetics among young adults is significantly increasing, affecting their self-confidence and self-image, especially with the major role being played by the media. Objective: The objective of this study was to assess the impact of dental esthetics on the psychological well-being of adult patients attending a university hospital in Saudi Arabia. Materials and Methods: A total of 613 patients attending university hospitals participated in this study by answering the online and printed version of the questionnaires. A Psychosocial Impact of dental aesthetics questionnaire was used in self-assessment for satisfaction with dental esthetics, and a self-perceived dental treatment needs. Collected data were analyzed using descriptive statistics and Chi-square tests. Results: The participants reported smile satisfaction with satisfied (52.4%) and highly satisfied (22.8%), while only 24.8% reported dissatisfaction. Tooth color was the most common cause of dissatisfaction (49.3%). Conclusions: The majority of the participants were satisfied with their smiles, however, a large percentage are still in need of further esthetic dental treatments as their smiles have a major impact on their social and psychological well-being. Hence, more public awareness programs should be directed to educate our community to make better choices of cosmetic dental procedures.